RepID as a potential biomarker and therapeutic target for lung neuroendocrine tumor - Jong-Uk Park; Jae-Hyun Jo; Sangjune Kim; Christophe E. Redon; Mirit I. Aladjem; Yuri Seo; Se Jin Jang; Sang-Min Jang (Scientific Reports)
Abstract Neuroendocrine tumor (NET) is a rare malignant tumor, notably small cell lung cancer (SCLC), a type of lung neuroendocrine tumor, which has a survival rate of less than 7%. Although various biomarkers including CHGA (Chromogranin A), INSM1 (Insulinoma-associated protein 1), and SYP (Synaptophysin) are extensively used for the diagnostic testing of NET, their diverse specificities and sensitivities are acknowledged as limitations. Here, we demonstrate that RepID (Replication initiation determinant protein), a component of CRL4 (Cullin-RING ubiquitin E3 ligase 4), holds promise as a biomarker for identifying NET and SCLC. Analysis of the Cancer Cell Line Encyclopedia (CCLE) via the CellMinerCDB portal reveals a high correlation between RepID transcript levels and mRNA expression of NE signature genes. Additionally, RepID protein is highly expressed in SCLC patient tissues and a subset of SCLC cell lines. Viability analysis following treatment with pevonedistat and SZL-P1-41 in SCLC cell lines and human SCLC-organoid models indicates that RepID expression determines the sensitivity to CRL-targeting anti-cancer drugs. These findings suggest that RepID represents a novel biomarker for NET and SCLC, and insights from RepID research in these cancers could lead to innovative therapeutic strategies.